ANALYSIS OF THE IMPLEMENTATION OF THE POLICY PP 36/2017, PMK-165 2017 POST FORGIVENESS TAX (POST-TAX AMNESTY ) - Suparmin, Suparmin (EAJ (Economic and Accounting Journal), 2018)
Taxes are the most important factors for the state finances to guarantee the continuity of national development without depending on natural resources and foreign aid. To encourage the compliance required taxs and expand the tax data base on 2016 published Act No. 11 The year 2016 about forgiveness tax (Tax Amnesty). Tax forgiveness Program given by the Government to the required taxs include the elimination of the tax should be are indebted, the elimination of tax administration and the elimination of the criminal sanction in the field of taxation of wealth obtained in 2015 and before that has not been reported in SPT.Although there are polemics at the beginning was launched. But there are benefits that are expected when PP-36/2017 policy implemented which will give the opportunity for Taxpayers who have followed the Tax Forgiveness Program but there are still the property which has not been or is not exposed in whole or for Taxpayers who qualify but it does not follow the tax forgiveness program so that the order of Article 18 of Act No. 11 The year 2016 about Tax Amnesty.In addition to the advantages there is also the downside to Taxpayers who follow the Tax Forgiveness program with Taxpayers who do not follow the tax forgiveness program. Taxpayers who have followed the Tax Forgiveness program, but by Fiskus has found wealth is not revealed it is considered as income when found the property that will be subject to Income Tax in accordance with the provisions of the legislation are speeding PPh plus the sanction of 200%.For Taxpayers who did not join the Program tax forgiveness when found wealth is considered as income when found incur Income Tax plus the sanction in accordance with the provisions of legislation on taxes